Thickness Dependence of The Surface Roughness of Micro Contact Deposited By Dc Magnetron Sputtering Technique - Muhammad Idzdihar , Idris; Nowshad, Amin; Puvaneswaran, Chelvanathan; Arith, Faiz (2014)

(untitled)
Integrated circuits are tested in final step of IC packaging to verify that required electrical connections are working properly. At present, Pogo Pins are used as electrical connection between IC lead and load board. Pogo pins caused different problems including indentation marks, blur marks, tilting, spring malfunction, high maintenance cost and etc. The present miniaturization trends towards higher performance, smaller and lighter product have resulted in an increasing demand for smaller pitch size and increase the issues of testing process with pogo pins. Pogo pins induced reliability problems when dealing with fine-pitch (< 0.5 mm) packages. New electrical conductive cell was designed in previous works. It was based on microstructures instead of pogo pins and consists of three different parts including polymer, metallic micro contactors and liquid metal. New Model was designed for QFP packages with 0.5 mm pitch size using simulation in previous years. Novel test socket mechanical design and analysis were successfully done by previous study. New models with new materials in different shapes were designed and the best one was achieved.